Cardiac biomarkers and left ventricular systolic function in former very preterm infants and term controls at preschool age - Höck, Michaela; Posod, Anna; Odri Komazec, Irena; Griesmaier, Elke; Ralser, Elisabeth; Pupp-Peglow, Ulrike; Kiechl-Kohlendorfer, Ursula (Frontiers in Pediatrics, 2024)
Introduction Due to improvements in perinatal care, survival rates of preterm infants have improved during the last decades, however, they are at risk of developing cardiovascular sequelae later in life. The aim of this study was to investigate cardiac biomarkers and left ventricular systolic function in former preterm infants in comparison to term controls at preschool age. Methods Five- to seven-year-old children born below 32 weeks of gestational age were included in the study. The control group consisted of same-aged children born at term. Basic data of study participants were collected by means of questionnaires and follow-up databases. At study visit, we recorded anthropometric data and blood pressure readings, determined high-sensitive cardiac troponin T (hs-cTnT) and N-terminal-pro-B type natriuretic peptide (NT-pro-BNP) concentrations and calculated fractional shortening (FS) and left ventricular mass (LVM). Results Term born (n=25; median gestational age 40.1 weeks) compared to preterm born infants (n=80; median gestational age 29.6 weeks) showed no significant differences in the median concentration of hs-cTnT (median 3.5 (IQR 3.5; 3.5) vs. 3.5 (3.5; 3.5) ng/l, p=0.328) and the median concentration of NT-pro-BNP (median 91.0 (IQR 40.8; 150.3) vs. 87.5 (50.1; 189.5) ng/l, p=0.087). FS and LVM/LVMI were not significantly different between the two groups. Conclusion At preschool age, we observed no significant difference in cardiac biomarkers and left ventricular systolic function in preterm infants. Further studies are warranted about cardiac biomarkers as potential prognostic tool for subclinical cardiac alterations after preterm birth.